(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
Roman artefacts comprised a samian sherd and some glass fragments, all probably redeposited. There were also eleven sherds of Scottish medieval gritty ware and thirty three post-medieval sherds.